2019
DOI: 10.32604/jrm.2019.07493
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation and Adsorption Property of Polyvinyl alcohol/Cellulose Nanocrystal/Graphene Composite Aerogels (PCGAs)

Abstract: The cellulose nanocrystals/graphene composite aerogel (CGA) and polyvinyl alcohol/cellulose nanocrystals/graphene composite aerogel (PCGA) were prepared by suspension titration, tert-butanol solution replacement and freeze-drying successively. The removal rates of methyl blue (MB) from water by CGA and PCGA were evaluated and the effects of additions, adsorption time, reaction temperature and pH value of CGA and PCGA on MB removal rate were discussed. It was found that the optimal concentrations of both CGA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This was because during the pyrolysis process of aerogels, the hydrogen bonds of the molecular chains were recombined after breaking down, thus forming a more regular network structure again. Therefore, more heat was needed to decompose these structures [32,33].…”
Section: Structural Differences Of Aerogels Prepared By Different Solsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was because during the pyrolysis process of aerogels, the hydrogen bonds of the molecular chains were recombined after breaking down, thus forming a more regular network structure again. Therefore, more heat was needed to decompose these structures [32,33].…”
Section: Structural Differences Of Aerogels Prepared By Different Solsmentioning
confidence: 99%
“…Forests 2019, 10, 749 12 of 16 recombined after breaking down, thus forming a more regular network structure again. Therefore, more heat was needed to decompose these structures [32,33]. Figure 10 shows the stress-strain curves of aerogels prepared under four different conditions.…”
Section: Differences In Thermal Stability Of Aerogels Prepared By Difmentioning
confidence: 99%
“…Herein, we demonstrated an approach to disperse multilayer graphene (MLG) in water with the cellulose nanocrystal (CNC) as adjuvant ( Wu et al, 2019b ). Cellulose, one of the most abundant, natural, and renewable biopolymers in the world, is widely present in biomasses like woods ( Wu et al, 2019c , 2020a , b ), corn stover ( Zhao et al, 2020 ), and tunicate ( Zhao et al, 2015 ), and can be metabolized by specific bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the features of inherent renewability, biodegradability, and biocompatibility make it an eco-friendly green material. In general, extraction from natural fibers through sulfuric acid hydrolysis is usually used to prepare CNC ( Wu et al, 2019b ). The negative charged sulfate groups in the CNC surface prepared by this method make them repel each other and result in good stability ( Jiang and Hsieh, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high thermal conductivity of graphene suggests that it can be applied to microelectronics and thermal management. Since Balandin (2011) discovered that graphene exhibited remarkably better thermal conductivity than conventional carbon nanotubes, graphene has been applied to heat management of high-power electronics, including thermal dissipation systems for chips and batteries in smartphones, tablets, smart VR systems, and wearable devices (Wu et al, 2019;Zheng et al, 2019;Yang et al, 2020). Many studies have shown that polymer composite thermal conduction capabilities can be improved significantly via the blending or grafting of graphene (Yu et al, 2007;Ji et al, 2014).…”
Section: Introductionmentioning
confidence: 99%